1987
DOI: 10.1149/1.2100839
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of Porous Ni / ZrO2 ‐  Y 2 O 3 Cermets

Abstract: The conductivity of porous normalNi/ZrO2‐Y2O3 cermets at 1000°C was determined as a function of Ni content between 15 and 50 volume percent (v/o) of total solids for two different zirconia particle sizes (23 and 47 m2/g). Below Ni contents of 30 v/o, ionic conduction through the zirconia phase dominated. At 30 v/o Ni, a greater than three order of magnitude increase in the conductivity was observed, corresponding to a change in mechanism to electronic conduction through the Ni phase. The conductivity of cerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(101 citation statements)
references
References 1 publication
9
90
1
1
Order By: Relevance
“…It is important that the YSZ in the electrolyte be well connected to the YSZ in the anode since this provides a conduction path for O 2− ions into the anode and increases the TPB available for reaction. Dees et al [2] have characterized the electronic conductivity of Ni/YSZ anodes and found that the volume % of Ni in the cathode required to obtain high electronic conductivity is~30% which is in accordance with percolation theory which predicts that this volume % is needed to form an interconnected Ni network.…”
Section: Ni/ysz Anodes -Current Statementioning
confidence: 59%
“…It is important that the YSZ in the electrolyte be well connected to the YSZ in the anode since this provides a conduction path for O 2− ions into the anode and increases the TPB available for reaction. Dees et al [2] have characterized the electronic conductivity of Ni/YSZ anodes and found that the volume % of Ni in the cathode required to obtain high electronic conductivity is~30% which is in accordance with percolation theory which predicts that this volume % is needed to form an interconnected Ni network.…”
Section: Ni/ysz Anodes -Current Statementioning
confidence: 59%
“…Figure 3, upper graph). The relationship has been described in the literature with a power law [10,11]. The trend for the theoretical relationship is included in the diagram and appears to represent the measured data well.…”
Section: Porositymentioning
confidence: 91%
“…It's non-requirement of a high energy sintering stage, offers an opportunity for cost reduction and complete elimination of high temperature induced defects such as cell warpage occasionally associated with existing processes. In SOFC technology, nickel aids fuel catalysation and electronic conductivity while YSZ in addition to preventing nickel from sintering at high SOFC operating temperatures of about 1000˚C, re-lieves the coefficient of thermal expansion (CTE) mismatch between the anode and electrolyte [8,9,10] (nickel -13 × 10 -6 /˚C & YSZ -10 × 10 -6 /˚C). High nickel content promotes cell cracking while too low a content and correspondingly high YSZ presence could compromise cell efficiency and performance [11].…”
Section: Introductionmentioning
confidence: 99%